Discourse toward Revising Mathematics Curriculum in Indonesia From Six Universal Mathematical Activities’ Perspective - Putra, Mulia (International Conference on Elementary Education, 2020)
This paper aims to describe one-decade mathematics curriculum condition revision in Indonesia. In one decade, there is a rapid transformation related to Indonesia curriculum including mathematics curriculum. In fact, the reason behind revising the curriculum tend to be political since the change itself happen along with the change of structure of government position, start from president until ministry of education and culture who have a big influence in changing or revising curriculum. However, the reason behind revising the curriculum is not focus in this discussion rather describing mathematics curriculum through three curricula transformation which are Competency Based Curriculum (KBK), School Based Curriculum (KTSP) and Curriculum 2013. The documents of mathematics curriculum from Junior High School grade VII will be used as a focus discussion. It shows that pattern in composing curriculum especially for one-decade mathematics curriculum is considering mathematics culture free and value less in the perspective on six universal mathematical activities